13.9%‐Efficiency and Eco‐Friendly Nonfullerene Polymer Solar Cells Obtained by Balancing Molecular Weight and Solubility in Chlorinated Thiophene‐Based Polymer Backbones. Issue 41 (22nd August 2019) - Jeon, Sung Jae; Han, Yong Woon; Moon, Doo Kyung
Abstract: To industrialize nonfullerene polymer solar cells (NFPSCs), the molecular design of the donor polymers must feature low‐cost materials and a high overall yield. Two chlorinated thiophene‐based polymers, P(F–Cl) and P(Cl–Cl), are synthesized by introducing halogen effects like fluorine (F) and chlorine (Cl) to the previously reported P(Cl), which exhibits low complexity. However, the molecular weights of these polymers are insufficient owing to their low solubility, which in turn is caused by introducing rigid halogen atoms during the polymerization. Thus, they show relatively low power conversion efficiencies (PCEs) of 11.8% and 10.3%, respectively. To overcome these shortcomings, two new terpolymers are designed and synthesized by introducing a small amount of 1, 3‐bis(5‐bromothiophen‐2‐yl)‐5, 7‐bis(2‐ethylhexyl)benzo[1, 2‐c:4, 5‐c′]dithiophene‐4, 8‐dione (BDD) unit into each backbone, namely, P(F–Cl)(BDD = 0.2) and P(Cl–Cl)(BDD = 0.2). As a result, both polymers remain inexpensive and show a better molecular weight–solubility balance, achieving high PCEs of 12.7% and 13.9%, respectively, in NFPSCs processed using eco‐friendly solvents. Abstract : This study presents a reasonable strategy for designing 2DBDT‐chlorinated thiophene‐based donor polymers with balanced molecular weight and solubility by modifying the structure of previously reported low cost P(Cl) to achieve high‐efficiency polymer solar cells (PSCs). As a result, the new P(Cl–Cl)(BDD = 0.2) reaches a high power conversion efficiency of 13.9% using eco‐friendly solvents for commercialization of PSCs.